Research on Management and Control of Miners’ Unsafe Behavior Based on Gray Theory - Shuicheng Tian; Guangtong Shao; Hongxia Li; Pengfei Yang; Qingxin Dang; Fujing Yuan (Shock and Vibration)
A large number of accidents and scientific researches show that miners’ unsafe behavior affects coal mine safety production seriously. In order to effectively reduce the incidence of miners’ unsafe behavior, to improve their safety level, and reduce accidents caused by it, this paper used gray relational analysis method to analyze the miners’ unsafe behavior of W mine and quantitatively calculated the risk value of miners’ unsafe behavior. The results showed that the risk value of unsafe behavior in violation of labor discipline was 0.4358, which was much higher than that of other miners’ unsafe behaviors. Therefore, unsafe behavior in violation of labor discipline was determined as the key point of control in the next stage. Then, GM (1, 1) method was used to establish a predicted model for unsafe behavior, to predict the number of unsafe behaviors in violating labor discipline in next quarter, and to determine reasonable unsafe behavior control target. This study plays a driving role in controlling unsafe behaviors of miners and improving safe production water of coal mine.